PENGARUH KOMPOSISI ETANOL-AIR DALAM PEMBENTUKAN PSEUDOPOLIMORFISME KLINDAMISIN HIDROKLORIDA - Anggraeni, Silvana
Solid active pharmaceutical compound could form solvates and hydrates pseudopolymorphism, including antibiotic solids. Pseudopolymorphism (hydrate/solvate) was the term used for the formation of the crystal lattice which involve water or other organic solvents. If the solvent was water, it called hydrates. And organic solvent as the solvent called solvates. Pseudopolymorphism (hydrate / solvate) has been widely reported to affect the physicochemical properties such as physical stability, flow rate, compactibility, compressibility, solubility, dissolution rate, and bioavaibility. Recently reported to be able to form clindamycin hydrochloride monohydrate ethanol solvate and monohydrate with ethanol-water (5:2). This study aimed to observe the effect of ethanol-water composition used in the recrystallization process of the formation of clindamycin hydrochloride monohydrate ethanol solvate and monohydrate. Clindamycin hydrochloride is recrystallized with various percentages of ethanol in water (95%, 80%, 70%, 60%, 50%, and 40%). Crystals formed were treated differently which was: fresh and storage for 48 hours at room temperature. Then the crystals were characterized by polarized microscopy to see the habit and size particle, FTIR, PXRD, DTA, and observation desolvatation / dehydratation process with polarized microscopy-plate heater. Clindamycin hydrochloride crystals which were forming from recrystallization with various percentages of ethanol in water could form mohohydrate ethanol solvates and hydrates crystals. The 60-95% ethanol shows IR spectra in wavenumbers 3517-3563 cm' which indicates incoporation ethanol in the crystal lattice, whereas crystals obtained from solvent 50 and 40% gave a peak at wavenumbers 3409-3482 cm-I which indicates hydrate formation. Difraktogram PXRD results showed differences in the crystal lattice of the monohydrate ethanol solvate and clindamycin hydrochloride monohydrate compared to the standardd. Monohydrate ethanol solvate diffraction peak's at 20 : 7.26 and 6.02 degrees, while hydrate's at 2 0 : 5.48 degree. However, monohydrate ethanol solvate and monohydrate of clindamycin hydrochloride crystals were unstable. It can be shown from the results of FTIR analysis, PXRD, DTA, and observations with a polarized microscopy of crystals that had been stored for 24 hours and have lost the character monohydrate and its ethanol solvate. In addition to effect on the formation of monohydrate ethanol solvate / monohydrate, ethanol was used affected the habit and particle size. Clindamycin hydrochloride crystals would arrange the monohydrate ethanol solvate and monohydrate pseudopolymorphism. Concentration of ethanol in water as which use as solvent will determine the kind of pseudopolymorphism were formed. Concentration of ethanol more than 70% formed monohydrate ethanol solvate, while less than 50% of ethanol would form monohydrate, and 60% of ethanol would form their mixture. However, monohydrate ethanol solvate and monohydrate of clindamycin hydrochloride were unstable. In addition to affecting the results of the formation of hydrates or solvates, the percentage of ethanol will affect the habit and particle size.